Dreaming in Byzantium and beyond - Angelidē, Christina; Calofonos, George T. (Ashgate, 2014)
This book - the first collection of studies on Byzantine dreams to be published - aims to demonstrate the importance of closely examining dreams in Byzantium in their wider historical and cultural, as well as narrative, context. The remarkable number of dream narratives in Byzantine hagiography, historiography, rhetoric, epistolography, and romance attests to the cardinal function of dreams as vehicles of meaning in politics, religion and literature. The essays provide a broad variety of perspectives, exploring gender, eroticism, Greco-Roman and Islamic influences, psychoanalysis and anthropol.